Presentation is loading. Please wait.

Presentation is loading. Please wait.

Introduction to Algebra

Similar presentations


Presentation on theme: "Introduction to Algebra"— Presentation transcript:

1 Introduction to Algebra
2 Introduction to Algebra Click on the computer image at the bottom right for a direct web link to an interesting Wikipedia Math Site. Prepared by: Richard Mitchell Humber College

2 CASE STUDY

3 2.1-Algebraic Expressions

4 2.1-DEFINITIONS-Pages 52 to 55
See WileyPLUS Glossary for Terms and Definitions

5 2.2-ADDITION AND SUBTRACTION OF ALGEBRAIC EXPRESSIONS

6 2.2-EXAMPLE 20-Page 56

7 2.2-EXAMPLE 24(c)-Page 57

8 2.2-EXAMPLE 25-Page 57

9 2.3-Integral Exponents

10 2.3-EXAMPLE 28(c)-Page 60

11 2.3-EXAMPLE 29(b) and 29(c)-Page 60

12 2.3-EXAMPLE 30(c) and 30(d)-Page 61

13 2.3-EXAMPLE 31(c) and 31(e)-Page 61

14 2.3-EXAMPLE 32(d) and 32(e)-Page 62

15 2.3-EXAMPLE 33(e)-Page 63

16 2.3-EXAMPLE 34(d)-Page 63

17 2.3-EXAMPLE extra

18 2.3-EXAMPLE 35(c) and 35(e)-Page 63

19 2.3-EXAMPLE 36(f)-Page 64

20 2.3-SUMMARY-Page 64 The Laws of Exponents

21 2.4-MULTIPLICATION OF ALGEBRAIC EXPRESSIONS

22 2.4-EXAMPLE 37(c)-Page 66 Multiply the following: (-p)(-q)(-r)(-s)
ANS: pqrs

23 2.4-EXAMPLE 40-Page 67 Multiply the following: (4a3b)(-3ab2)
= (4)(-3)(a3)(a1)(b1)(b2) = -12a(3+1)b(1+2) = -12a4b3 ANS: -12a4b3

24 2.4-EXAMPLE 41-Page 67 Multiply 5x2, -3xy, and –xy3z
= (5x2)(-3xy)(-xy3z) = (5x2)(-3x1y1)(-x1y3z1) = +15x(2+1+1)y(1+3) z1 = +15x4y4z1 ANS: 15x4y4z

25 2.4-EXAMPLE 42-Page 67 Multiply 3x2 by 2axn = (3x2)(2axn)
= (3)(2)(a)(x2)(xn) = 6ax(2+n) ANS: 6axn+2

26 2.4-EXAMPLE 43-Page 68 Multiply the following (without brackets):
2x(x – 3x2) = (2x)(x) + (2x)(-3x2) = (2x1)(x1) + (2x1)(-3x2) = 2x2 – 6x3 ANS: 2x2 – 6x3

27 2.4-EXAMPLE 44(a)-Page 68 Multiply the following (without brackets):
-3x3(3x2 – 2x + 4) = (-3x3)(3x2) + (-3x3)(-2x) + (-3x3)(4) = (-3x3)(3x2) + (-3x3)(-2x1) + (-3x3)(4) = -9x5 + 6x4 – 12x3 ANS: -9x5 + 6x4 – 12x3

28 2.4-EXAMPLE 47(b)-Page 69 Multiply the following (without brackets):
3{2[4(w – 4) – (x + 3)] – 2} – 6x = 3{2[4(w – 4) – x – 3] – 2} – 6x = 3{2[4w – 16 – x – 3] – 2} – 6x = 3{2[4w – x – 19] – 2} – 6x = 3{8w – 2x – 38 – 2} – 6x = 3{8w – 2x – 40} – 6x = 24w – 6x – 120 – 6x = 24w – 12x – 120 ANS: 24w – 12x – 120

29 2.4-EXAMPLE 48-Page 69 Multiply the following (without brackets):
(x + 4)(x – 3) = (x)(x) + (x)(-3) + (4)(x) + (4)(-3) = x2 – 3x + 4x – 12 = x2 + x – 12 ANS: x2 + x – 12 NB: Also known as the F.O.I.L. Rule

30 2.4-EXAMPLE 50(a)-Page 69 Multiply the following (without brackets):
(x – 3)(x2 – 2x + 1) = (x)(x2) + (x)(-2x) + (x)(1) + (-3)(x2) + (-3)(-2x) + (-3)(1) = x3 – 2x2 + x – 3x2 + 6x - 3 = x3 – 5x2 + 7x – 3 ANS: x3 – 5x2 + 7x – 3

31 2.4-EXAMPLE 50(b)-Page 69 Multiply the following (without brackets):
(2x + 3y – 4z)(x – 2y – 3z) = (2x)(x)+(2x)(-2y)+(2x)(-3z)+(3y)(x)+(3y)(-2y )+(3y)(-3z) +(-4z)(x)+(-4z)(-2y)+(-4z)(-3z) = 2x2 – 4xy – 6xz + 3xy – 6y2 – 9yz – 4xz + 8yz + 12z2 = 2x2 – 6y2 + 12z2 – xy – 10xz - yz ANS: 2x2 – 6y2 + 12z2 – xy – 10xz – yz

32 2.4-EXAMPLE 51-Page 69 ANS: 2x3 – 5x2 – x + 6
Multiply the following (without brackets): (x – 2)[(x + 1)(2x – 3)] = (x – 2)[(x)(2x) + (x)(-3) + (1)(2x) + (1)(-3)] = (x – 2)[2x2 – 3x + 2x – 3] = (x – 2)[2x2 – x – 3] = (x)(2x2) + (x)(-x) + (x)(-3) + (-2)(2x2) + (-2)(-x) + (-2)(-3) = 2x3 – x2 – 3x – 4x2 + 2x + 6 = 2x3 – 5x2 – x + 6 ANS: 2x3 – 5x2 – x + 6

33 2.4-EXAMPLE 52-Page 70 ANS: x3 – 3x2 + 3x – 1
Multiply the following (without brackets): (x – 1)3 = (x – 1)[(x – 1)(x – 1)] = (x – 1)[(x)(x) + (x)(-1) + (-1)(x) + (-1)(-1)] = (x – 1)[x2 – 2x + 1] = (x)(x2) + (x)(-2x) + (x)(1) + (-1)(x2) + (-1)(-2x) + (-1)(1) = x3 – 2x2 + x – x2 + 2x – 1 = x3 – 3x2 + 3x – 1 ANS: x3 – 3x2 + 3x – 1

34 2.4-EXAMPLES-Pages 70 to 71 Special Cases: Tricks:
(x + 2)(x – 2) = x2 – 22 (x + 2)2 = (x + 2)(x + 2) = x2 + 4x + 4 (x – 2)2 = (x – 2)(x – 2) = x2 – 4x + 4 (x – 3)3 = (x – 3)(x – 3)(x – 3) = x3 – 9x2 + 27x – 27 Tricks: Perfect Square Trinomials 9x2 – 12x + 4 = (3x – 2)2

35 2.5-Division of Algebraic Expressions

36 2.5-EXAMPLE 63(a)-Page 76

37 2.5-EXAMPLE 64-Page 76

38 2.5-EXAMPLE 66-Page 76

39 2.5-EXAMPLE 67-Page 77

40 2.5-EXAMPLE 68-Page 77

41 2.5-EXAMPLE 69-Page 77

42 Copyright © 2012 John Wiley & Sons Canada, Ltd.
All rights reserved. Reproduction or translation of this work beyond that permitted by Access Copyright (The Canadian Copyright Licensing Agency) is unlawful. Requests for further information should be addressed to the Permissions Department, John Wiley & Sons Canada, Ltd. The purchaser may make back-up copies for his or her own use only and not for distribution or resale. The author and the publisher assume no responsibility for errors, omissions, or damages caused by the use of these programs or from the use of the information contained herein.


Download ppt "Introduction to Algebra"

Similar presentations


Ads by Google